2006
DOI: 10.1097/00008483-200601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Regular Walking and Long-term Maintenance of Outcomes After Pulmonary Rehabilitation

Abstract: Findings suggest that participation in regular exercise such as walking after completing pulmonary rehabilitation is associated with slower declines in overall health-related quality of life and walking self-efficacy as well as less progression of dyspnea during activities of daily living. Regular exercise after rehabilitation may be protective against increases in dyspnea symptoms and perceived limitations in walking which are both characteristic of progressing chronic lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(60 citation statements)
references
References 24 publications
6
43
3
8
Order By: Relevance
“…3,[37][38][39][40] We sought to extend those findings by analyzing the effect of ongoing exercise after pulmonary rehabilitation. Contrary to the findings of Heppner et al, 41 who found that subjects who continued to walk regularly after a pulmonary rehabilitation program utilized health care as often as those who did not, our findings show that fewer subjects visited the emergency department or required hospitalization after pulmonary rehabilitation. In the subgroup of subjects who did require an emergency department visit or hospitalization, however, the average number of emergency department visits or hospital days was unchanged after pulmonary rehabilitation.…”
Section: Long-term Exercise Adherence and Health-care Utilizationcontrasting
confidence: 99%
“…3,[37][38][39][40] We sought to extend those findings by analyzing the effect of ongoing exercise after pulmonary rehabilitation. Contrary to the findings of Heppner et al, 41 who found that subjects who continued to walk regularly after a pulmonary rehabilitation program utilized health care as often as those who did not, our findings show that fewer subjects visited the emergency department or required hospitalization after pulmonary rehabilitation. In the subgroup of subjects who did require an emergency department visit or hospitalization, however, the average number of emergency department visits or hospital days was unchanged after pulmonary rehabilitation.…”
Section: Long-term Exercise Adherence and Health-care Utilizationcontrasting
confidence: 99%
“…Of the analyses comparing standard rehabilitation and the standard treatment, only 1 showed that the former had positive effects (10) on the symptoms (Figure 3). One study (28) showed that resistance exercises improved the symptoms of dyspnea in comparison with baseline data, although there were no differences between the groups in terms of patient perception of dyspnea after the 6MWT. Combining rehabilitation with the use of tiotropium, (17) noninvasive ventilation, (15) or hypertonic saline (31) had no additional effect on symptoms when compared with the standard rehabilitation program.…”
Section: Symptomsmentioning
confidence: 99%
“…Patients with COPD who maintain activity have less dyspnoea during daily activity, better health-related quality of life [7], and enhanced long-term functional [8], physiological and psychological outcomes [9]. In order to develop and implement cost-effective physical activity maintenance interventions in the clinical setting, however, more information is needed on the sociodemographic and disease-related characteristics of individuals with differing patterns of physical activity following rehabilitation.…”
mentioning
confidence: 99%